2003
DOI: 10.1093/0195063864.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Pride, Faith and Fear

Abstract: Islam is spreading rapidly in sub‐Saharan Africa, home of more than 150 million Muslims. African Islam is local Islam, responsive to local histories in cultures as diverse as the countries considered in this study – Nigeria, Sudan, Senegal, Kenya, and South Africa. Islam provides a source of communal identity to those experiencing rapid change, populations affected by secularization, unemployment, corrupt and ineffectual governments, and the intrusions of global media. The spread of Islam ascends as respect fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…With each conflict between Muslims and Christians also its perception changes and "religious identity moves up the scale of importance." 61 The ideological positions harden, with fatal consequences in a country with small arms relatively easily available and great numbers of young people without any perspectives at all. If Nigerian politics does not succeed in achieving considerable changes, conflicts will continue and are likely to increase in number and intensity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With each conflict between Muslims and Christians also its perception changes and "religious identity moves up the scale of importance." 61 The ideological positions harden, with fatal consequences in a country with small arms relatively easily available and great numbers of young people without any perspectives at all. If Nigerian politics does not succeed in achieving considerable changes, conflicts will continue and are likely to increase in number and intensity.…”
Section: Resultsmentioning
confidence: 99%
“…We resolve to preserve the unity of purpose and action in international affairs which we have forged among ourselves in this historic Conference; to safeguard our hard-won independence, sovereignty and territorial integrity; and to preserve among ourselves the fundamental unity of outlook on foreign policy so that a distinctive African Personality will play its part in co-operation with other peaceloving nations to further the cause of peace. 61 Zahlenmäßig hätte der Casablanca-Entwurf bei der Abstimmung keine Chance gehabt. Die meisten Stimmen wären wohl auf den Monrovia-Entwurf gefallen (19 der 31 anwesenden Staaten waren in dieser Gruppe).…”
Section: Conclusiomentioning
confidence: 99%
See 1 more Smart Citation
“…Quinn (2003) found that by 3 to 4 months of age infants reacted with a novelty preference to visual displays where an object was depicted as above versus below a horizontal line, as long as object identity was constant across trials. By 7 months infants were able to overcome this limitation, reliably distinguishing above versus below even when the object depicted varied (dot, dollar sign, plus sign, etc.…”
Section: Cognitive Basis Of Dynamic Event Wordsmentioning
confidence: 97%
“…Because of the capacity for mental representation, a child who has eaten a cookie can imagine that another might be given to replace it. Children's perceptual development begins at birth, research has demonstrated changes in the ability to interpret spatial events over time (e.g., Quinn 2003). The capacity to process absent events requiring mental representation has a later developmental trajectory (e.g., Hakke and Somerville 1985;Piaget and Inhelder 1969).…”
Section: Cognitive Basis Of Dynamic Event Wordsmentioning
confidence: 99%